Populism, Instability, and Rupture in Sustainability Transformations. Issue 7 (10th November 2021) - Wanvik, Tarje I.; Haarstad, Håvard
Abstract : The recent surge in populist politics in Europe and North America has challenged many of the policies aimed at advancing sustainable shifts. In this article we argue that this surge necessitates a rethinking of transition and transformation. The mainstream perspective on transitions understands it largely as the proliferation and upscaling of innovative technologies and policy frameworks. We recast sustainability transitions and transformations as continuous processes of assembly and disassembly, driven by rupture and instability. Rather than seeing populist resurgence as a "barrier" to change toward sustainability, we argue that these ruptures and instabilities should be considered inherent to the transformation process itself. The recent local election in Bergen, Norway, witnessed the surge of a new "anti-elite" political party dedicated to protesting road tolls that finance public transport. We hold that although such movements certainly pose challenges to sustainable transitions, they also provide opportunities for revitalizing democratic politics—moving beyond postpolitical managerial governance and inviting new concerns into local and urban transformation processes.